Econometric Analysis With Panel Data: Measuring Relations And Contributions Of Influential Factors On Income Per Capita Across Districts In Sragen Regency - Raditya Teguh Anugraha; I Wayan Suletra; Yusuf Priyandari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
Levels of prosperity of an area is measured by income per capita. Income per capita is derived from regional income divided by mid-year population number. In Srgaen Regency, income per capita amongdistricts very different significanly so a reaserch is needed to know the causes of this variability. In general, many factors affect the income per capita and each factor may have different effect in form of relationship and level of contribution. To solve these problems this reaserch used econometric which is the result of a certain outlook on the role of economics, consists of the application of mathematical statistics to economic data to lend empirical support to the models constructed by mathematical economics and to obtain numerical results. Panel data which is a combination of data type cross-section and times series is used in this study. To combine the indicators variables that have different units is used factor analysis. Regression model pooled least square (PLS), fixed effect, and random effect was tested to get the most representative models describing the relationship between income per capita and the factors that influence. From the analysis it shown that not all district have the same model. Thus the Government of Sragen Regency can treatment on different district based on the factors that influence and encourage these factors so that the income per capita is increasing.